Experimental induction and monitoring of liver abscesses in cattle with ultrasonography - Lechtenberg, K.F.; Avery, T.B.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We have demonstrated that ultrasonography can be used to visualize liver abscess in live cattle. We have also developed a nonsurgical method of catheterizing the bovine portal vein and experimentally inducing liver abscesses by inoculating the portal vein with Fusobacterium necrophorum bacteria.
Keywords: Beef; Liver abscess; Ultrasonography